IGRADIENT-CONTINUOUS YEAST CULTIVATION FOR THE ALCOHOL PRODUCTION FROM MOLASSES - Levandovskiy L. V.; Myhailyk V. S. (Biotechnologia Acta, 2017)
This work objective is to find the technological conditions for the intensification of yeast growth in the gradient-continuous yeast cultivation process. Experiments on four sequential yeast chemostats (connected into a battery) demonstrated broad possibilities to influence the metabolic activity of yeast and the alcohol production depending on the content of molasses introduced into the second, third and fourth yeast generators. Adding the molasses according to the 3:2:1 scheme in quantities, which are sufficient to achieve the initial concentration of solids of 26.5 g/100 cm3 to the end of the process resulted in high accumulation of yeast in the medium (up to 99 g/dm3).